2014
DOI: 10.4103/0972-124x.128199
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the gingival biotype based on the measurement of the dentopapillary complex

Abstract: Background:The gingival morphology of the maxillary anterior region plays an important role in determining the final esthetic outcome. Knowledge of the periodontal biotype is of fundamental importance because the anatomical characteristics of the periodontium, such as gingival thickness, gingival width and alveolar bone morphology, will determine periodontium behavior when submitted to physical, chemical, or bacterial injury or during periodontal or implant surgical procedures and orthodontic treatment.Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
(19 reference statements)
0
12
0
2
Order By: Relevance
“…The anatomical characteristics of the periodontium, such as gingival thickness, gingival width and alveolar bone morphology, will determine periodontium behavior when it is submitted to physical, chemical, or bacterial injury ( Malhotra et al, 2014 ). The periodontium is mainly the interdental spaces between the molars and premolars, which are susceptible to gingival inflammation ( Kassebaum et al, 2014 ; Eke et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical characteristics of the periodontium, such as gingival thickness, gingival width and alveolar bone morphology, will determine periodontium behavior when it is submitted to physical, chemical, or bacterial injury ( Malhotra et al, 2014 ). The periodontium is mainly the interdental spaces between the molars and premolars, which are susceptible to gingival inflammation ( Kassebaum et al, 2014 ; Eke et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Outros estudos que reproduziram essa metodologia e que também classificaram os fenótipos em fino ou espesso, concluíram que o teste de transparência à sondagem é um método que, quando devidamente padronizado, é suficientemente reprodutível e confiável 10,[13][14][15][16] . Dentre as principais características encontradas após a determinação dos fenótipos nessas pesquisas, foi visto que o fenótipo gengival fino apresenta tecido mole mais delgado com menor faixa de mucosa ceratinizada, papilas interdentais mais longas e estreitas.…”
Section: Discussionunclassified
“…Dentre as principais características encontradas após a determinação dos fenótipos nessas pesquisas, foi visto que o fenótipo gengival fino apresenta tecido mole mais delgado com menor faixa de mucosa ceratinizada, papilas interdentais mais longas e estreitas. Já o fenótipo espesso foi caracterizado por apresentar maior faixa de mucosa ceratinizada com aspecto denso e fibrótico, bem como papilas mais curtas e largas 10,[13][14][15][16] .…”
Section: Discussionunclassified
“…The thickness of the gingiva is also influenced by the papillary height,[ 12 ] crown width and height ratio, and the width of keratinized gingiva. [ 13 ] The gingival thickness in this study was found to increase from G1 to G4.…”
Section: Discussionmentioning
confidence: 99%